Improving Student Learning Outcomes through the CTL Model Aided by Media Pancasila Diagram - Anugraheni, Anggie Widari; Fardani, Much Arsyad; Santoso, Santoso (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
This research is based on low students’ learning outcomes. The purpose of this study is to improve the learning outcomes of grade V students of elementary school (Sekolah Dasar Negeri/SDN) 8 Gondosari using the Contextual Teaching and Learning model assisted by Pancasila diagram media. This research was a classroom action research. This research was done in two cycles. The subject of this research was 17 students of class V SDN 8 Gondosari. The data was collected through interview, observation, and writing test. The data was analyzed qualitatively and quantitatively. The results of the first cycle showed the percentage of 64.71%. For the second cycle, the percentage was 88.24%. Meanwhile, the results of interviews and observations obtained from teachers and students, namely for teacher skills in the first cycle, obtained a score of 66%, while in the second cycle 92% for student learning activities in the first cycle with a score of 58%, there was an increase in the second cycle of 73%. Based on these findings, it can be concluded that the use of Contextual Teaching and Learning model assisted by Pancasila diagram media can improve the learning outcomes of grade V students of SDN 8 Gondosari.